Teaching The Science Of Kalam In Selected Higher Education Institutions In Malaysia - Mustafa Kamal Bin Amat Misra Misra; Nurhanisah Binte Senin; Muhammad Faiz Mukmin Bin Abdul Mutalib (UMSU, 2023)
The science of Kalam is a part of knowledge born from the manifestation of logic. The history of Islamic civilization saw it play a role as the basis for the explosive development of new knowledge which later became known as science, chemistry and physics. The presence of its pioneers who are also skilled in philosophy, makes this science usually paired with debates that are philosophical and not in the scope of science. However, the context of the study of knowledge in the world in general, and even in Malaysia in particular, it is only known among groups with a background in the study of usul al-din majors. This paper focuses on the teaching of science of Kalam in selected Higher Education Institutions in Malaysia. This study uses a qualitative methodology with a survey method. As a limitation of the study, in addition to focusing on informants and responses from the background of usul al-din studies, the study will also select selected respondents and informants from backgrounds other than Islamic studies that are deemed suitable with strong justification.